STUDI LITERATURE REVIEW PENGARUH STRATEGI DIVERISFIKASI TERHADAP KINERJA PERUSAHAAN DAN MANAJEMEN LABA - Muttia Anggreini; Ferdinand Aldo; Kezia Hany Josefin Rondonuwu; Vanka Auliani; Carmel Meiden (Politeknik Raflesia Press, 2022)
This study aims to identify the elements that can be associated with diversification. Diversification, namely the company carries out a strategy by adding new products but having linkages with existing products (concentric diversification). In other words, diversification has the aim of maximizing the size of the business so as to maximize the profits derived from the expansion of the business segments owned so as to improve the company's performance. However, with diversification, there are also opportunities in matters relating to earnings management which can be explained by agency theory.